Activities and Outputs from SME and MNC Collaboration on R&I Projects - Nesse, Per J.; Opsahl, Kristoffer (Nordic and Baltic Journal of Information & Communications Technologies, 2023)
The fifth generation (5G) of telecommunication systems is creating new business opportunities for many industry verticals. Managing the innovation process is risky and calls for collaboration with various ecosystem stakeholders to meet the demands of technology, business, and customers. This article investigates the activities and output of participation in collaborative research and innovation (R&I) activities for Small and Medium Sized Enterprises (SMEs) and Multi National Corporations (MNCs) and how they engage with such activities. A survey was conducted with a non-random sample of 42 respondents involved in R&I projects and further supplemented with three in-depth interviews of a subset of the survey respondents. Our key findings indicate that SMEs benefit from technology-related activities and access to decision makers in MNCs. Heavy-handed bureaucracy in projects is a friction point for SMEs, which prefer development speed over scheduled reports and deliverables. In contrast, MNCs benefit from business-related activities by advertising technology to clients, suppliers, and downstream business models. Suggested improvements include additional client needs assessments, trialing of technology and service concepts, and dissemination of the results of R&I activities. SMEs and MNCs view establishing relationships with other partners as valuable for accessing key competencies and vertical industry ecosystems. Our findings provide novel insight in the collaboration of R&I projects with SMEs and MNCs and contributes to the business ecosystem and open innovation literature. Further research should include follow-up studies of the SME–MNC collaboration towards commercialization of innovative 5G use cases.